Controversies concerning the diagnosis and treatment of bipolar disorder in children - Johnston Josephine; Parens Erik (BMC, 2010)
Abstract This commentary grows out of an interdisciplinary workshop focused on controversies surrounding the diagnosis and treatment of bipolar disorder (BP) in children. Although debate about the occurrence and frequency of BP in children is more than 50 years old, it increased in the mid 1990s when researchers adapted the DSM account of bipolar symptoms to diagnose children. We offer a brief history of the debate from the mid 90s through the present, ending with current efforts to distinguish between a small number of children whose behaviors closely fit DSM criteria for BP, and a significantly larger number of children who have been receiving a BP diagnosis but whose behaviors do not closely fit those criteria. We agree with one emerging approach, which gives part or all of that larger number of children a new diagnosis called Severe Mood Dysregulation or Temper Dysregulation Disorder with Dysphoria. Three major concerns arose about interpreting the DSM criteria more loosely in children than in adults. If clinicians offer a treatment for disorder A, but the patient has disorder B, treatment may be compromised. Because DSM's diagnostic labels are meant to facilitate research, when they are applied inconsistently, such research is compromised. And because BP has a strong genetic component, the label can distract attention from the family or social context. Once a BP diagnosis is made, concerns remain regarding the primary, pharmacological mode of treatment: data supporting the efficacy of the often complex regimens are weak and side effects can be significant. However, more than is widely appreciated, data do support the efficacy of the psychosocial treatments that should accompany pharmacotherapy. Physicians, educators, and families should adopt a multimodal approach, which focuses as much on the child's context as on her body. If physicians are to fulfill their ethical obligation to facilitate truly informed consent, they must be forthcoming with families about the relevant uncertainties and complexities.